PENGARUH STRUKTUR MODAL, UKURAN PERUSAHAAN, PERTUMBUHAN PERUSAHAAN DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN (STUDI KASUS PERUSAHAAN TRANSPORTASI DAN LOGISTIK DI BEI) - Rakhmatika Septiana; Taufiq Andre Setiyono (LPPM PoliteknikPratamaKendal- Universitas Sains Dan Teknologi Komputer, 2026)
This study aims to analyze the effect of capital structure, company size, company growth, and profitability on company value in the transportation and logistics sector listed on the Indonesia Stock Exchange. The research approach used is quantitative, utilizing secondary data from annual financial reports, which are then analyzed using multiple linear regression. The results show that capital structure has a negative effect on company value, while company size and company growth have a positive effect. Profitability also shows a negative effect, indicating that high profits are not always viewed positively by the market if they are considered unsustainable. Simultaneously, the four independent variables were able to explain 32.3% of the variation in company value, while the rest was influenced by other factors outside the research model. These findings emphasize the importance of optimal capital structure management, increased operational efficiency, sustainable growth, and stable profit quality as strategies to increase company value.